Short- and long-term memory: effects of ageing and genetic risk and resilience to Alzheimer's disease - Čepukaitytė, G (2021)
Healthy memory processes are essential for leading a normal life. In particular, this thesis will focus on short-term memory (STM) and long-term memory (LTM). STM is our ability to store limited amounts of information over short periods of time, while LTM refers to our capacity to retain near-unlimited amounts of information over prolonged periods of time. Traditionally, these two types of memory have been studied independently. As a result, our knowledge of the relationship between them has remained limited. In this thesis, I develop well-controlled tasks to compare STM and LTM for the same type of information, formed during equivalent encoding circumstances, and reported in similar ways. Results show that STM and LTM for the same type of information are indeed related. Furthermore, by studying both STM and LTM in cognitively healthy young, middle-aged and older adults, I show that the relationship between these two memory functions remains stable across normal ageing, suggesting some degree of overlap in the underlying neural mechanisms. I also attempt to characterise this relationship in individuals who are at an increased genetic risk of developing Alzheimer’s disease, namely, carriers of the apolipoprotein E gene (APOE) ε4 allele, although limited sample size hinders the interpretation of findings. In Chapter 1 of this thesis, I review the literature that supports STM-LTM dichotomy, in addition to studies that suggest similarities between these memory functions. I also provide an overview of the effects of healthy ageing on STM and LTM, and how these memory functions change in the presence of different APOE alleles. In Chapters 2 and 3, I focus on healthy ageing and its effects on STM and LTM. In Chapter 2, these effects are studied in APOE ε2 carriers and non-carriers. In Chapter 3, I introduce two novel continuous-report tasks that enable analogous probing of both types of memory in order to measure the relationship between them. This task is employed in Chapter 4 to assess memory performance in middle-aged APOE ε4 carriers and non-carriers, with an aim to use similar tasks to characterise the effects of this allele on memory in the future. In Chapter 5, I discuss the implications of my findings and the areas in which this research could be extended and improved.